THE EFFECTIVENESS OF SOCIALISATION OF THE IMPLEMENTATION OF BILATERAL CROSS-BORDER TRADE AGREEMENTS: A LITERATURE REVIEW ON THE IMPROVEMENT OF THE WELFARE OF BORDER COMMUNITIES - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2026)
This study aims to evaluate the effectiveness of socialisation of bilateral trade agreements between countries and its impact on improving the welfare of border communities through a literature review. Effective socialisation is crucial to the understanding and active participation of the community in utilising the economic opportunities provided by these agreements. However, the implementation of socialisation often faces obstacles such as limited access to information and inadequate infrastructure. Literature review indicates that participatory socialisation approaches, adaptable to local contexts, and supported by cross-sectoral synergies can significantly enhance the implementation outcomes of bilateral trade agreements. The findings of this study provide strategic recommendations for policymakers and programme implementers to enhance socialisation capacity to promote sustainable welfare for border communities.